2021
DOI: 10.3389/fphys.2021.729925
|View full text |Cite
|
Sign up to set email alerts
|

IL-6/STAT3 Induced Neuron Apoptosis in Hypoxia by Downregulating ATF6 Expression

Abstract: Background: Neuron apoptosis, regulated by endoplasmic reticulum (ER) stress in the hippocampus, is an essential factor influencing the cognitive impairment induced by hypobaric hypoxia. Hypoxia mainly changes the activating transcription factor (ATF6) pathway of ER stress. However, the role of ATF6 in neuron survival, apoptosis, and upstream regulation is still controversial.Methods: We established a hypobaric hypoxia-induced C57BL/6 murine model and cell lines exposed to 1% hypoxia, including PC12 and HT22. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…HIF1 , NRSF , SMAD3 , and STAT3 target genes were enriched in Thoc6 fs/fs E9.5 forebrain (Figure S6G). HIF-1 and STAT3 can induce apoptosis in response to hypoxia (Greijer and van der Wall, 2004; Zhou et al, 2021), which is consistent the observed elevation of apoptosis in Thoc6 fs/fs E9.5 neuroepithelium (Figures 3E and 3F). SMAD3 signaling is activated by TGF-β to promote cortical differentiation (Vogel et al , 2010), suggesting shared disruption of TGF-β signaling in both human and mouse model systems.…”
Section: Resultssupporting
confidence: 87%
“…HIF1 , NRSF , SMAD3 , and STAT3 target genes were enriched in Thoc6 fs/fs E9.5 forebrain (Figure S6G). HIF-1 and STAT3 can induce apoptosis in response to hypoxia (Greijer and van der Wall, 2004; Zhou et al, 2021), which is consistent the observed elevation of apoptosis in Thoc6 fs/fs E9.5 neuroepithelium (Figures 3E and 3F). SMAD3 signaling is activated by TGF-β to promote cortical differentiation (Vogel et al , 2010), suggesting shared disruption of TGF-β signaling in both human and mouse model systems.…”
Section: Resultssupporting
confidence: 87%
“…Pathological neovascularization is a major feature of OIR, 34 , 35 which is mainly manifested by the rapid and massive proliferation of endothelial cells to form vascular clusters. 21 , 36 In our study, we found a significantly elevated LGALS3BP in the retinas of OIR mice that was positively correlated with angiogenesis, suggesting that LGALS3BP may play a proangiogenic role in the OIR model. Given these results, we knocked down LGALS3BP in HMC3 cells for relative functional and phenotypic analysis in vitro, and we further found that LGALS3BP in HMC3 cells regulates the proliferation, migration, and tube formation of HUVECs.…”
Section: Discussionsupporting
confidence: 57%
“…Accumulating reports have revealed that the expression patterns of CHOP and Grp78, two target genes of ATF6, are dampened subsequent to ATF6 knockdown (Dadey et al., 2016; Zhou, Zhong, et al., 2021). In the study, we discovered the reduction of CHOP and Grp78 protein levels and Ca 2+ concentration and the rise of SW620 cell proliferation, which demonstrated that knockdown of ATF6 partially negated the proapoptotic effect of curcumin on CRC cells.…”
Section: Discussionmentioning
confidence: 99%